RANCANG BANGUN SISTEM PENDETEKSI KEBAKARAN BERBASIS IOT DAN SMS GATEWAY MENGGUNAKAN ARDUINO - Sari, Viona Novita; Zulkifli; Antony, Fery (Universitas Indo Global Mandiri, 2023)
Fire is the occurrence of unwanted and difficult to control fires. Fires are not only caused by human or technical factors and even cause many victims, fires are also catastrophic events that occur unexpectedly when they occur. In order to mitigate the catastrophes that develop in outer space, this research can design, build, and test systems that can communicate directly over the Internet using IoT technology that sends data via SMS and telephone. This research allows the manufacture and improvement of detectors that have previously been tried with different tools and different versions. This test determines the performance of fire and smoke detectors, carried out 10 times at a distance of is less than or equal to 35 cm. The detection system uses Arduino as the main component. a microcontroller that processes input data from two sensors, namely the smoke/gas sensor Mq-2 and the fire sensor Ky-026 as detectors for the two sensors. can be used as a fire alarm system, using the LCD screen as the output value, and the GSM SIM800L v1 module, used as an information service, automatically sends notifications as SMS to smartphones. Therefore, the higher the fire and smoke values tested, the more sensitive and the value increases. Therefore, this study concludes that the fire sensor Ky-026 and smoke sensor Mq-02 can detect distances up to is less than or equal to 35 cm. Data messages can be received within 7.2 seconds